Exploratory study of metacognitive beliefs about coping processes in prolonged grief symptomatology - Wenn, Jenine; O'Connor, Moira; Breen, Lauren; Rees, Clare (Routledge, 2018)
© 2018 Taylor & Francis. Despite research examining the role of metacognitive beliefs about coping processes in maintaining psychological disorders, to date, no studies have explored their role in the maintenance of prolonged grief. Twelve semistructured interviews were conducted with bereavement specialists and bereaved people with elevated grief to identify metacognitive beliefs about coping processes relevant to prolonged grief. Analysis revealed several metacognitive beliefs potentially driving maladaptive coping processes used by people with prolonged grief symptomatology. Findings may underpin the development of interventions that aim to modify unhelpful metacognitive beliefs that perpetuate maladaptive coping processes.